Identity and territory: Jewish perceptions of space in antiquity - Ben-Eliyahu, Eyal (University of California Press, 2019)
"The book examines the role of territory in Jewish identity in antiquity and, more specifically, the role of Jewish perceptions of space and place in identity. The time period covered extends from the Second Temple period to the first centuries CE. The examination relates to a variety of approaches to the land, its borders, and its holy places as expressed by Jewish writers of the period, located both inside and outside of the land. The book's central assertion is that the territory's status and scope and the way in which sacred spaces are perceived all depend on Jewish identity in all of its complexity and diversity"--Provided by publisher